Issues relating to CPF as a retirement scheme. - Leong, Kian Meng. (2008)
The post-war baby boomers will soon fall within the age group of 60 years and above, turning Singapore into one of the world's fastest aging population. According to the Ministry of Health, the projected number of elderly in Singapore in the year 2030 will form 25% of the total population, which is as high as 850,000! Issues relating to CPF as a retirement scheme are discussed in different parts in three main chapters. It will revolve around retirement and how investment and housing schemes of CPF make a difference in retirement by increasing retirement income. After that, the limitations of our project and recommendations on what the government could do to increase CPF savings for a betterretirement will also be discussed as well.